Errors in heat detection are costly - Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1988)
Attention to heat detection will decrease reproduction losses and costs associated with extended calving intervals and high culling rates. Errors in diagnosing heat (errors of commission) and missed heats (errors of omission) are the major errors of a heat detection program. Priority must be given to heat detection to improve reproductive efficiency and reduce the costs of reproductive failure on dairy farms.; Dairy Day, 1988, Kansas State University, Manhattan, KS, 1988;
Keywords: Kansas Agricultural Experiment Station contribution; no. 89-107-S; Dairy; Heat detection; Reproductive efficiency; Costs